2008
DOI: 10.1158/0008-5472.can-08-0410
|View full text |Cite
|
Sign up to set email alerts
|

Nitric Oxide Is a Key Component in Inflammation-Accelerated Tumorigenesis

Abstract: Nitric oxide (NO . ), an important signaling molecule and a component of inflammatory response, is involved in tumorigenesis. However, the quantity of NO. and the cellular microenvironment influences the role of NO . in tumor development. We used a genetic strategy to test the hypothesis that an inflammatory microenvironment with an enhanced level of NO . accelerates spontaneous tumor development. C. parvuminduced inflammation and increased NO . synthase-2 (NOS2) expression coincided with accelerated spontaneo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
82
1
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 98 publications
(84 citation statements)
references
References 49 publications
(61 reference statements)
0
82
1
1
Order By: Relevance
“…There is now strong evidence that NO itself, through its proinflammatory effects, may play an important role in carcinogenesis (35). The increase in iNOS activity may well be a consequence of the proinflammatory environment in the colon of Gstp-null Apc Min mice.…”
Section: Discussionmentioning
confidence: 99%
“…There is now strong evidence that NO itself, through its proinflammatory effects, may play an important role in carcinogenesis (35). The increase in iNOS activity may well be a consequence of the proinflammatory environment in the colon of Gstp-null Apc Min mice.…”
Section: Discussionmentioning
confidence: 99%
“…Higher levels of NO· can be produced by an inducible nitric oxide synthase (iNOS, also known as NOS2) in different cell types, but mainly in macrophages, upon infection to kill pathogens (reviewed in reference 9). The higher levels of NO· produced by iNOS have been implicated in various human inflammatory diseases and neurodegenerative diseases (reviewed in references 9 and 12) and in chronic inflammation-related tumorigenesis (18,33). Recent studies have also shown that chemical-generated higher levels of exogenous NO· can induce tumor cell apoptosis in vitro and in animal studies (37; reviewed in reference 1), raising interests in therapeutic exploration of NO·-releasing reagents as antitumor prodrugs.…”
mentioning
confidence: 99%
“…It is claimed that p53 À / À NOS2 þ / þ C57BL/6 mice, which display greater NO production, experience accelerated spontaneous tumor development, compared with p53 À / À NOS2 À / À mice. 65 In contrast, increased iNOS expression was also reported to be cytotoxic for tumor cells, since accumulated NO would trigger p53-mediated growth arrest and apoptosis. 66 With the guardian p53 absence, accumulated NO would impair T-cell function and, in turn, facilitate tumor progression.…”
Section: Discussionmentioning
confidence: 99%